En busca del lector implícito en tres versiones del relato de la niña obediente - Ana Sofía Ramírez Heatley (Universitat Autònoma de Barcelona, 2010)
This paper is a comparative analysis of "The Storyteller", by Saki, “Cuento de la niña condecorada” by Jorge Ibargüengoitia and "Super Dooper Jezebel" by Tony Ross: three works aimed directly or indirectly at younger readers, which share a single archetype or motif:  that of the obedient, overly perfect young girl who behaves more like an adult than a child. This examination of the similarities and differences between the three versions of the good-girl story, from the perspective of reception theory, highlights the role played by the implicit reader as an intrinsic element of the work's artistic make-up. Using different resources, and from their very structure, the three works conjure up the presence of an active reader who sees events coming, sets off the ironic and humorous games, uncovers meaning, interprets and, above all, generates that magical alliance between work and reader that breathes life into the text. This paper traces the steps of a pre-determined reader in three stories that condemn a character who, in the quest for perfection, falls into the horrific trap of embodying it.